Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
musisz skorzystać ze wzoru skróconego mnożenia
[tex](a-b)^{2}=a^{2} -2ab+b^{2}[/tex]
czyli masz
[tex]f(x)=4-(x^{2} -2x+1)=4-x^{2} +2x-1=-x^{2} +2x+3[/tex]
a = -1
b = 2
c = 3
[tex]f(x)=4-(x-1)^{2} \\\\f(x)=4-(x^{2} -2x+1)\\\\f(x)=4-x^{2} +2x-1\\\\f(x)=-x^{2} +2x+3~~szukan~~postac~~ogolna~~funkcji~~kwadratowej~~gdzie:\\\\a= -1,~~b=2,~~c=3\\\\Aby~~wyznaczyc~~postac~~ogolna~~funkcji~~kwardatowej~~korzystalam\\\\ze~~wzoru~~skroconego~~mnozenia:\\\\(a-b)^{2} =a^{2} -2\cdot a\cdot b + b^{2} ~~\\oraz ~~pamietam~~o~~zmianie~~znaku~~gdy~~przed~~nawiasem~~jest~~znak~~"-"[/tex]